Evaluation of prevalence and cause of endodontic treatment of permanent molars in 10-year-old children of Riyadh, Saudi Arabia - Dalia Alharthi; Reema K Abumelha; Deema M AlOjayen; Nouf S Alanezi; Reema M Aldakheel; Abdulaziz S Abumelha (Wolters Kluwer Medknow Publications, 2024)
The study aimed to assess the prevalence and cause of endodontic treatment in the first permanent molars of children aged ten in Saudi Arabia. Out of 824 children, 104 had dental caries, with a prevalence rate of 12.62%. The research revealed that the most involved teeth were mandibular left first molar, followed by mandibular right first molar, maxillary left first molar, and maxillary right first molar. Majority of patients had grossly decayed teeth, followed by caries, restorations, and endodontic treatment. The study emphasizes the importance of early dental consultations to reduce morbidity and financial burden on parents.